2012
DOI: 10.1194/jlr.m031559
|View full text |Cite
|
Sign up to set email alerts
|

Assessing mechanisms of GPIHBP1 and lipoprotein lipase movement across endothelial cells

Abstract: The lipolytic processing of triglyceride-rich lipoproteins (e.g., chylomicrons, very low density lipoproteins) by lipoprotein lipase (LPL) is the central event in plasma triglyceride metabolism and plays a crucial role in the delivery of lipid nutrients to parenchymal cells (e.g., adipocytes, myocytes) ( 1-4 ). LPL is synthesized by parenchymal cells and secreted into the interstitial spaces, but it needs to reach the capillary lumen in order to hydrolyze the triglycerides in plasma lipoproteins. Recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 39 publications
3
76
0
Order By: Relevance
“…These findings may have considerable in vivo significance in light of recent data showing that, in humans, serum ANGPTL4 levels do not correlate with plasma triglyceride levels and that LPL travels bidirectionally across endothelial cells (24,25). These data have led to the suggestion that ANGPTL4 could inhibit LPL in the subendothelial space rather than on the endothelial surface (25). Here, we report our data showing a noncompetitive mechanism for ANGPTL4 inhibition of LPL and discuss its possible physiological implications.…”
Section: Lplmentioning
confidence: 67%
See 2 more Smart Citations
“…These findings may have considerable in vivo significance in light of recent data showing that, in humans, serum ANGPTL4 levels do not correlate with plasma triglyceride levels and that LPL travels bidirectionally across endothelial cells (24,25). These data have led to the suggestion that ANGPTL4 could inhibit LPL in the subendothelial space rather than on the endothelial surface (25). Here, we report our data showing a noncompetitive mechanism for ANGPTL4 inhibition of LPL and discuss its possible physiological implications.…”
Section: Lplmentioning
confidence: 67%
“…The protein GPIHBP1 binds to the endothelium of capillary cells where it provides a platform for LPL to process triglycerides from lipoproteins (41). GPIHBP1 also helps transport LPL across the endothelial cells, and a recent study has shown that this transport is bidirectional (25,42). ANGPTL4 could thus inhibit LPL in either the subendothelial space or on the surface of the capillary endothelium, and a number of recent studies support the former option.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our studies shed some light on what the possible efficacy of ANGPTL4 might be in different physiological contexts. It has been previously suggested that the most prevalent site of ANGPTL4-mediated LPL inactivation may be in the interstitial space (11,39). Concentrations of ANGPTL4 in the interstitial space of various tissues are not known, but they are likely to be high in tissues such as adipose where gene expression is high (20).…”
Section: Discussionmentioning
confidence: 99%
“…GPIHBP1 provides an important platform for LPL-mediated hydrolysis of chylomicron triglycerides. Davies et al [78] showed that GPIHBP1 was effective in transporting LPL from the basolateral to the apical surface of endothelial cells. Recently, it has been suggested that LPL and GPIHBP1 move bidirectionally across the cell surface, however, the understanding of the molecular processes of the transport remains incomplete [79].…”
Section: Lipoprotein Lipase and Chylomicron Metabolismmentioning
confidence: 99%